2008
DOI: 10.1007/s10712-008-9048-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Continental Hydrology and Glaciology Signals from GRACE: A Review

Abstract: Since its launch in March 2002, the Gravity Recovery and Climate Experiment (GRACE) has provided a global mapping of the time-variations of the Earth's gravity field. Tiny variations of gravity from monthly to decadal time scales are mainly due to redistributions of water mass inside the surface fluid envelops of our planet (i.e., atmosphere, ocean and water storage on continents). In this article, we present a review of the major contributions of GRACE satellite gravimetry in global and regional hydrology. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(130 citation statements)
references
References 69 publications
(93 reference statements)
1
123
0
1
Order By: Relevance
“…Wahr et al (1998) reported that the largest-amplitude and most varied time-dependent signals are related to water storage variability on land. Ramillien et al (2008a) concluded that GRACE satellite gravimetry offers a very interesting alternative remote sensing technique to measure changes in total water storage over continental areas. This includes ice, snow, surface waters, soil moisture and groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Wahr et al (1998) reported that the largest-amplitude and most varied time-dependent signals are related to water storage variability on land. Ramillien et al (2008a) concluded that GRACE satellite gravimetry offers a very interesting alternative remote sensing technique to measure changes in total water storage over continental areas. This includes ice, snow, surface waters, soil moisture and groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…By closing the water balance equation, components such as groundwater can be estimated. However, this is made possible only by the availability of integrated mass change that can be derived from gravity observations (Schmidt et al 2006;Ramillien et al 2008). Separating the contributions of water mass sub-reservoirs (i.e., surface waters, soil moisture, groundwater) is thus a challenge for the next GRACE-type mission, especially for estimating deep water changes that globally remain unknown.…”
Section: Estimating Continental Water Storage and Freshwater Fluxesmentioning
confidence: 99%
“…For instance, seasonal variations of hundreds of millimeter of equivalent water height have been detected by GRACE in large tropical basins (around ±500 mm in the Amazon basin, Ramillien et al 2008). Measuring water height variations with a 10-cm precision at 150-200-km resolution would allow us, for instance, to recover mass variations in basins such as the Rhine and Danube catchments, which cannot be studied with available data.…”
Section: Summary Of Emotion Science Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…de Jeu et al, 2008]. The twin-satellites of the Gravity Recovery and Climate Experiment (GRACE) measure variations in the gravity field of the earth with approximately monthly resolution [Ramillien et al, 2008;Tapley et al, 2004;Rodell and Famiglietti , 1999]. Regional accumulations of water (e.g.…”
Section: Terrestrial Variablesmentioning
confidence: 99%